If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 11 = -81 Reorder the terms: 11 + n = -81 Solving 11 + n = -81 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + n = -81 + -11 Combine like terms: 11 + -11 = 0 0 + n = -81 + -11 n = -81 + -11 Combine like terms: -81 + -11 = -92 n = -92 Simplifying n = -92
| ln(y)=-5*x+ln(c) | | =7(y+3) | | x-9+3(5x+4)=2(x+6) | | 3x(x-6)-(10x-6)= | | 3(-3x+2)=-7(x+3)-2 | | x^2-3-y=0 | | 0.25(x+2)-5=12 | | (10y+6)-(17y+8)= | | x^2+100x=0 | | (y^2+2y)(y^3-2y^2+1)= | | 5=20x+(10x*x) | | -2=0.2-6 | | 6x-4=23-3y | | x^2+12x+9=4 | | 3x-2=7x-3 | | 3a+5b=b+7b | | X+3=-12+6x | | 6(5x-11)=48x | | .25+X=45 | | 7m=2+5m | | -73=3e | | 10=-2x-2(-4x+4) | | 2(2w+3x)-3(2w-3x)= | | T(x)=19-(-3) | | 9m=-30+3m | | 4x+4+2x=9x+1 | | Y=7(x+1) | | 5x^3+43x^2-18x=0 | | 10m=28+3m | | 12=22.50x | | 180=(4x+7)+(2x+53) | | 88=-8(a-5) |